Electrochemical characterization of platinum based catalysts for fuel cell applications - Thobeka, Adonisi (University of the Western Cape, 2014)
Magister Scientiae - MSc === Fuel cells convert chemical energy from a fuel into electricity through chemical reaction with oxygen. This possesses some challenges like slow oxygen reduction reaction (ORR), overpotential, and methanol fuel cross over in a direct methanol fuel cell (DMFC). These challenges cause inefficiency and use of higher amounts of the expensive platinum catalyst.Several binary catalysts with better ORR activity have been reported. In this study we investigate the best catalyst with better ORR and MOR performances and lower over-potentials for PEMFC and DMFC applications by comparing the in-house catalysts (10%Pt/C, 20%Pt/C,30%Pt15%Ru/C, 40%Pt20%Ru/C, 30%PtCo/C, 20%Pt20%Cu/C and 20%PtSn/C) with the commercial platinum based catalysts (10%Pt/C, 20%Pt/C, 20%Pt10%Ru/C, 20%PtCo/C,20%PtCu/C and 20%PtSn/C) using the cyclic voltammetry and the rotating disk electrode to determine their oxygen reduction reaction and methanol tolerance. HRTEM and XRD techniques were used to determine their particle size, arrangement and the atomic composition. It was observed that the 20%Pt/C in-house catalyst gave the best ORR activity and higher methanol oxidation current peaks compared to others catalysts followed by 20%Pt10%Ru/C commercial catalyst. The 20%PtCo/C commercial, 30%PtCo/C in-house and 20%PtSn/C in-house catalysts were found to be the most methanol tolerant catalysts making them the best catalysts for ORR in DMFC. It was observed that the ORR activity of 20%PtCo/C commercial and 30%PtCo/C inhouse catalysts were enhanced when heat treated at 350 0C. From XRD and HRTEM studies, the particle sizes were between 2.72nm to 5.02nm with little agglomeration but after the heat treatment, the particles were nicely dispersed on the carbon support.